Painting as an Investment Opportunity in a Developing Economy - Kafaru, Abiodun Babatunde; Adeshina, Kelani Fatai (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025DO - 10.58709/niujhu.v10i1.2098, 2025)
This paper discusses the potentials of painting as a form of investment opportunities in Nigeria. Painting as an aspect of creativity has emerged since 20 th -21 st century as a major means of generating income opportunities for art collectors, foreign enthusiast, culture lovers, investors, active business men and future projectors in the business world. However, this business potential in painting is not limited to only business mogul and entrepreneurs, but also to some working middle class-civil servants have acute mercantile acumen engage in buying paintings to secure their future after retirement.  Prominent artists are often commissioned to produce quality and interesting paintings that appeals to the public taste in painting which also stands the test of time thus earning unprecedented returns at public auctions, exhibitions, and public bazaars in many parts of the world. Therefore, this paper also mentioned and discussed in details the values found in paintings as artwork - as it relates to investment in a mono economy like Nigeria. It is worthy to note, however, that there is great value in collecting paintings as alternative source of income thereby creating wealth for business men who understands the intrinsic pleasure from creativity of Nigerian cultural traditions in expanding personal and collective prosperity. On the other hand, the paper will also highlight the challenges facing the art industry - which includes low patronage, lack of funding to the artist and the limited sponsor/ art patrons, cost of materials and low public awareness, and the absence of a well-structured art market to engage art lovers and viewers. It further highlights the success stories of notable Nigerian artists and galleries, showcasing the opportunities for economic growth through the art sector. However, it is noteworthy in showcasing the practices of foreign countries where there is need for strategic investment, institutional support, and public-private collaboration to reveal the economic value of painting in Nigeria as well as other climes. Ultimately, the paper interrogates market potentials in arts through the instrument of painting as a tangible asset of cultural prosperity, propagation and appreciation. In the midst of high inflation and unfavorable economic climate, Nigeria can transform its art industry into a significant driver of wealth creation, employment, and cultural preservation. This paper aims to contribute to the discourse on art’s economic potential, particularly painting in inspiring policies and initiatives that position painting as a sustainable investment avenue for populace of Lagos, Nigerians and Sub region of West Africa. Keyword: Visual Art, Art Industry, Wealth creation, Economy challenges, Investment